Nitric Oxide (NO) System in Major Depression: Studies on NO Synthase Inhibitors as Antidepressant Agents - Dhir, Ashish; K. Kulkarni, Shrinivas (Current Enzyme Inhibition, 2016)
Nitric oxide is being explored for the treatment of neuropsychiatric disorders since decades. The molecule has shown to alter different neurotransmitters comprising norepinephrine, serotonin, glutamate and dopamine and thus plays an important role in the neurobiology of major depression. A large number of studies have depicted a dual-nature of this molecule in the pathophysiology of major depression and related neuropsychiatric disorders. It is well known that an enzyme responsible for the production of nitric oxide in the body viz. Nitric Oxide Synthase (NOS) is expressed in different areas of the brain. Interestingly, multiple antidepressants have shown to alter the levels of nitric oxide in the body, as demonstrated through animal studies. When determined using human subjects, patients suffering from major depression have altered levels of nitric oxide. With this background, we presented here a review gathering different studies describing the role of this small molecule in the neurobiology of major depression. Some of the studies conducted in our laboratory, exploring the role of L-arginine-nitric oxide-cyclic guanosine monophosphate signaling pathway in the effect of various conventional and novel antidepressants, have been listed here. It is our hypothesis that nitric oxide modulating antidepressants may be the future line of treatment in patients suffering from major depression, especially in cases of pharmacoresistant depression.
Keywords: NO-mediated depression